Skeletal muscle ([London] : BioMed Central Ltd., 2011)
A peer-reviewed, open access, online journal that publishes articles investigating molecular mechanisms underlying the biology of skeletal muscle. A wide range of skeletal muscle biology is included: development, metabolism, the regulation of mass and function, aging, degeneration, dystrophy and regeneration. The emphasis is on understanding adult skeletal muscle, its maintenance, and its interactions with non-muscle cell types and regulatory modulators.
Description based on: 2011, 1:1; title from PDF caption (publisher's Web site, viewed June 22, 2011).
Latest issue consulted: 2017, 7:19 (viewed Oct. 4, 2017).
Keywords: Musculoskeletal system -- Periodicals; Musculoskeletal system; Muscle, Skeletal; Physiology; Electronic journals